Comparison of the Effectiveness of Piper Crocatum and Sour Turmeric Acid for Healing Time - Lestari, Dewi; Usman, Andi Nilawati; Alam, Gemini; Hadju, Veni; Husin, Farid; Sartini, Sartini (Universitas Islam Negeri Mataram, 2022)
Maternal mortality (MMR) is still 359 per 100,000 live births, and the expected target is still far from what was proclaimed in 2030, the number of 70 per 100,000 live births. Based on data from WHO (Word Health Organization), in 2015, the deaths were around 2.7 million cases caused by perineal injuries. According to IDHS data (Indonesian Demographic and Health Survey), in 2017, the maternal mortality rate (MMR) was 305 per 100,000 live births caused by an infection in the perineal wound. The total maternal mortality rate (MMR) in various provinces in Indonesia has decreased from 4,226 to 4,221. In 2019 the maternal mortality rate (MMR) was most contributed by bleeding (30.3%) and postpartum infection (5%). This study aimed to determine the differences in the effectiveness of red betel and turmeric acid in the complementary wound healing treatment in postpartum women. This study was a quasi-experimental pretest-posttest control group design with a total sampling method by giving three intervention and control groups, as many as 30 postpartum women with perineal wounds grades I and II according to the inclusion criteria with the group given red betel, tamarind, and turmeric. Control group at Anutapura General Hospital Palu. Perineal wound care using the REEDA scale (Redness, Edema, Ecchymosis, Discharge, and Approximation). The results showed a difference in the effectiveness of red betel and turmeric acid on perineal healing. The average Mann-Whitney statistical test results were on the 5th and 7th days (P-Value < 0.005). This study shows that Piper crocatum can accelerate perineal wound healing and become an alternative for complementary therapy and perineal wound healing.